Pediatric's first aid (Snake bite/gigitan ular) - Muhd Helmi, Muhd Alwi; Anuar, Muhamad Azamin; Mohamad Khairi, Siti Nur Lina; Ahmed, Ebrahim Adel Ali (2021)
Training kit for nursery and kindergarten teachers on how to assess and treat snake bite children.